Pengaruh Edukasi Melalui Video terhadap Pengetahuan Ibu Nifas Tentang Teknik Menyusui di RSUD Mgr. Gabriel Manek, SVD., Atambua, Belu - Ahmad Mumtaz Tauba; Yusfina Modesta Rua; Melkianus Ratu; Paskalis Malafu Usfinit (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This community service activity was carried out with the aim of increasing the knowledge of postpartum mothers regarding breastfeeding techniques through educational media in the form of videos. The low understanding of postpartum mothers regarding the correct breastfeeding techniques can have an impact on the effectiveness of breastfeeding and the overall health of the baby. This activity was carried out at the Mgr. Gabriel Manek, SVD., Atambua Regional Hospital, Belu, involving postpartum mothers as participants. This project included identifying educational needs, making educational videos that were appropriate to local conditions and culture, and evaluating participants' knowledge before and after the intervention. The results showed a significant increase in the level of knowledge of postpartum mothers after receiving education through videos. This program has been proven to have a positive impact on increasing postpartum mothers' understanding of the correct breastfeeding techniques, and can be used as a model for educational interventions based on visual media in other health facilities. This article describes the methodological approach, results, and practical benefits of this community service activity.